Controllable boron doping of carbon nanotubes with tunable dopant functionalities: an effective strategy toward carbon materials with enhanced electrical properties. Issue 118 (16th November 2015) - Chiang, Wei-Hung; Chen, Guan-Lin; Hsieh, Cheng-Yu; Lo, Shen-Chuan
Abstract : An atmospheric-pressure substitution reaction to produce B-doped CNTs with controllable and uniform B distribution has been demonstrated. Abstract : We present a two-step postgrowth substitution reaction route to produce boron-doped carbon nanotubes (BCNTs) with controllable B dopant concentration and uniform B atom distribution under atmospheric pressure. The unique two-step postgrowth substitution reaction route comprised a simple wet-chemistry-assisted pretreatment and an atmospheric-pressure carbothermic reaction. Extensive materials characterizations confirmed that BCNTs with uniform B dopant distribution and controllable B atomic concentration from 0.40 to 3.92 atomic percent (atom%) can be produced by controlling the reaction time and temperature under atmospheric pressure in the developed method. The film-based electrical sheet resistance measurement indicates that the averaged electrical sheet resistances of the as-fabricated CNT-based films can be improved from 1520 ± 197.56 to 43.67 ± 12.63 Ω per square with 2.09 atom% B concentration in the doped CNTs. High-resolution X-ray photoelectron spectroscopy (HRXPS) characterization suggests that the B–C–O bonding types and concentrations in the as-produced BCNTs may play an important role in the nanotube electrical properties. Our study provides a methodology to tailor the material properties of carbon-based materials.